2014
DOI: 10.1016/j.clnu.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Association between nutrition and the evolution of multimorbidity: The importance of fruits and vegetables and whole grain products

Abstract: This study provides the first evidence of an association between nutrition and evolution towards multimorbidity. More precisely, greater consumption of fruits and vegetable and whole grain products consumption appear to lower the risk of multimorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 29 publications
6
96
3
Order By: Relevance
“…A recent study using the Jiangsu Longitudinal Nutrition Study from China showed a statistically significant association between high levels of fruit/vegetable intake and healthier stages in the evolution of multimorbidity. 13 Previous studies have also reported differences in the association of fruit/vegetable intake and chronic conditions and mortality by gender. A population-based study from Japan found a reduced risk of cardiovascular mortality associated with vegetable intake in women but not men.…”
Section: Comparison With Current Literaturementioning
confidence: 99%
“…A recent study using the Jiangsu Longitudinal Nutrition Study from China showed a statistically significant association between high levels of fruit/vegetable intake and healthier stages in the evolution of multimorbidity. 13 Previous studies have also reported differences in the association of fruit/vegetable intake and chronic conditions and mortality by gender. A population-based study from Japan found a reduced risk of cardiovascular mortality associated with vegetable intake in women but not men.…”
Section: Comparison With Current Literaturementioning
confidence: 99%
“…It has also been shown that regular consumption of FV facilitate the prevention of asthma, iron deficiency anaemia 6 and mental disorders 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies focused on the phenomenon which demonstrated that, the decrease in fruits and vegetables intake is positively correlated with an increase in NCDs incidence (Ruel et al, 2014;Negi et al, 2016;Gostin et al, 2017). Since, it's proved that fibers and vitamins present only in fruits and vegetables protect against vascular diseases, equilibrate blood sugar and enhance antioxidant system in the organism.…”
Section: Discussionmentioning
confidence: 99%